Utilizing Regulatory T Cells Against Rheumatoid Arthritis - Haque, Mohammad; Fino, Kristin; Lei, Fengyang; Xiong, Xiaofang; Song, Jianxun (Frontiers in Oncology, 2014)
Regulatory T (Treg) cells are essential for normal immune surveillance systems, and their dysfunction leads to development of diseases, such as autoimmune disorders. CD4+ CD25+ Treg cells are well-known suppressive cells which express the transcription factor Foxp3, are indispensable for the maintenance of immune self-tolerance and homeostasis by suppressing aberrant or excessive immune response. Other Foxp3- Treg cells include Tr1, Th3, CD8+CD28-/-, and Qa1-restricted T cells; however, the contribution of these Treg cells to self-tolerance, immune homeostasis as well as preventing autoimmunity is not well defined. Here we discuss the phenotypes and function of Foxp3+ Treg cells and the potential use of such Treg cells against rheumatoid arthritis. Of note, even though most expanded populations of Foxp3+ Treg cells exhibit suppressive activity, tissue-associated or antigen-specific Treg cells appear superior in suppressing local autoimmune disorders such as rheumatoid arthritis. In addition, utilizing tissue-associated Foxp3+ Treg cells from stem cells may stable Foxp3 expression and avoid induction of a potentially detrimental systemic immunosuppression.